2020
DOI: 10.1101/2020.04.14.042002
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A transcription regulatory network within the ACE2 locus may promote a pro-viral environment for SARS-CoV-2 by modulating expression of host factors

Abstract: IntroductionA novel severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) was recently identified as the pathogen responsible for the COVID-19 outbreak. SARS-CoV-2 triggers severe pneumonia, which leads to acute respiratory distress syndrome and death in severe cases. As reported, SARS-CoV-2 is 80% genetically identical to the 2003 SARS-CoV virus. Angiotensin-converting enzyme 2 (ACE2) has been identified as the main receptor for entry of both SARS-CoV and SARS-CoV-2 into human cells. ACE2 is normally e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 58 publications
(1 reference statement)
1
14
0
Order By: Relevance
“…ACE2 is repressed in pulmonary cells -a finding corroborated by other studies 56,57 -but inducible in gastrointestinal cells (Fig. 5).…”
supporting
confidence: 88%
“…ACE2 is repressed in pulmonary cells -a finding corroborated by other studies 56,57 -but inducible in gastrointestinal cells (Fig. 5).…”
supporting
confidence: 88%
“…Regulatory elements in the ACE2 gene control the transcription of PIR (pirin), a negative regulator of NF-κB subunit RELA (p65). SARS-CoV-2 disruption of ACE2 is proposed to reduce PIR expression ( Fadason et al., 2020 ). PIR is proposed to function as a reversible switch that enables NF-κB response to changes in redox levels (oxidative stress) in the cell nucleus ( Liu et al., 2013 ).…”
Section: Cytokine Storm Featuring High Expression Of Il-6 and Tnf-αmentioning
confidence: 99%
“…The Genotype-Tissue Expression (GTEx) database revealed that SNP rs6629110 was associated with greater expression of ACE2 [ 5 ], although researchers were not able to confirm the link between variants in the ACE2 gene and COVID-19 [ 10 ]. The SNP rs2106806 was among those included in a recent study aimed at describing a transcription regulatory network within the ACE2 locus in the context of SARS-CoV-2 infection, but no correlation was found [ 11 ]. Here, we show that the minor A allele within rs2106806 increases the risk of critical COVID-19.…”
Section: Discussionmentioning
confidence: 99%